A Study on the Client’s Charter in the Teluk Wanjah Dental Clinic, Kedah - Loke, Shuet Toh; Roslan, Husniyati (Malaysian Public Health Physicians’ Association, 2005)
The objective of this study was to evaluate compliance to the clients' charter in a dental clinic and factors that may affect the updating of the charter. Our clients' charter states that registration time is within 10 minutes and waiting~room time before being seen by the dentist is within 30 minutes. Convenience sampling was carried out over two weeks. Only j)atients above 12 years . treated by dental officers were included. Data recorded included registration and waiting~room time, treatment time, punctuality of patients and workload of officers. There were a total of 532 patients (407 wa!i,-in/outpatients, 125 appointments). Results show that the mean waiting~room time for all patients was not compliant to the clients' charter (42.7 ± 23.8 min for wal1<.~in; 44.9 ± 32.7 min for appointments). Only 33% were seen within 30 min whilst about 23% waited for more than 60 minutes. The mean registration time (17.9 ± 12.8 min) was non-compliant everyday except on Thursdays where there were very few patients. Waiting time for elderly patients was not statistically significant from the younger patients. About 36% of appointment patients were seen within 30 minutes; although half of them were late. Extractions, dentures and examination and diagnosis (£&0) took the shortest time with about 88%,91% and 98% completed within 30 minutes respectively. There was variable individual speed and number of patients managed by different operators, although the majority was first-year dental officers. Factors that may contribute to waiting time included number of patients per day, operator and punctuality of patients.